Artificial Intelligence Accountability in Positive Law - Siregar, Dahris (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Artificial intelligence (AI) has developed rapidly in recent years, making judgments and executing tasks in ways comparable to decisions made by the human brain. These technological advances allow AI to replace or complement human work in various fields, but they also raise complex legal questions regarding accountability for the actions it performs. This study employs a normative juridical research methodology, which emphasizes the analysis of laws and regulations, concepts, principles, and legal theories, using literature as the primary data source. The findings show that AI, despite its advanced capabilities, remains a legal object rather than a legal subject. In accordance with Government Regulation No. 71 of 2019 on the Implementation of Electronic Systems and Transactions in Indonesia, AI cannot be considered a legal entity with independent rights and obligations. Consequently, AI cannot be held legally accountable for its actions, as it operates under human creation, programming, and direction. Responsibility for any consequences arising from the use of AI lies with the individuals or institutions that develop, operate, and control it. This study highlights the importance of establishing a clear legal framework to regulate AI applications, ensuring that technological innovation aligns with legal certainty and accountability. It concludes that while AI may imitate human decision-making, it lacks autonomy in the legal sense and therefore cannot bear responsibility under positive law.